Disparities in Gallbladder Cancer: Epidemiology, Molecular Mechanisms, and Clinical Implications - Om Saswat Sahoo; Gurpeet Singh Gill; Arnab Nayek; Nidhi Bhardwaj; Kailash Chand Kurdia; Saurabh Galodha; R Chetan; Ruby Dhar; Subhradip Karmakar (Molecular Biology Reports, 2026)

Evolutionary co-option of endogenous retroviruses: syncytins as regulators of placental development and disease - Anamta Gul; Om Saswat Sahoo; Neha Kashyap; Sunil Singh; Anubhuti Rana; Lavanya Gupta; Swati Ajmeriya; Indrani Mukherjee; Ruby Dhar; Nihar R. Nayak; Subhradip Karmakar (Molecular Biology Reports, 2026)

Postharvest γ-Aminobutyric Acid Treatment Modulates Antioxidant Metabolism and Delays Quality Deterioration of Litchi Fruit - Nilanksha; Preeti Singh; Hidayatullah Mir; Ruby Rani; Mohammed Wasim Siddiqui; Fozia Homa; Shashi Prakash (Applied Fruit Science, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Effect of environmental air pollutants on placental function and pregnancy outcomes: a molecular insight - Sunil Singh; Isha Goel; Smita Tripathi; Ashok Ahirwar; Megha Kumar; Anubhuti Rana; Ruby Dhar; Subhradip Karmakar (Environmental Science and Pollution Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Spatiotemporal Shift of Soil Microbes in Conservation Agriculture under a Rice-Based Cropping System at the New Alluvial Zone of Lower Gangetic Plain - Puja Singh; Susanta Dutta; Siddhartha Mukherjee; Niharendu Saha; Bishnuprasad Dash; Samrat Ghosh; Biswabara Sahu; Ruby Pate; Ahana Dey; M Jaison; Tufleuddin Biswas; Biswapati Mandal (Journal of Soil Science and Plant Nutrition, 2024)

The first ensemble of kilometer-scale simulations of a hydrological year over the third pole - Emily Collier; Nikolina Ban; Niklas Richter; Bodo Ahrens; Deliang Chen; Xingchao Chen; Hui-Wen Lai; Ruby Leung; Lu Li; Alzbeta Medvedova; Tinghai Ou; Praveen Kumar Pothapakula; et al. (Climate Dynamics, 2024)
An accurate understanding of the current and future water cycle over the Third Pole is of great societal importance, given the role this region plays as a water tower for densely populated areas downstream. An emerging and promising approach for skillful climate assessments over regions of complex terrain is kilometer-scale climate modeling. As a foundational step towards such simulations over the Third Pole, we present a multi-model and multi-physics ensemble of kilometer-scale regional simulations for the hydrological year of October 2019 to September 2020. The ensemble consists of 13 simulations performed by an international consortium of 10 research groups, configured with a horizontal grid spacing ranging from 2.2 to 4 km covering all of the Third Pole region. These simulations are driven by ERA5 and are part of a Coordinated Regional Climate Downscaling EXperiment Flagship Pilot Study on Convection-Permitting Third Pole. The simulations are compared against available gridded and in-situ observations and remote-sensing data, to assess the performance and spread of the model ensemble compared to the driving reanalysis during the cold and warm seasons. Although ensemble evaluation is hindered by large differences between the gridded precipitation datasets used as a reference over this region, we show that the ensemble improves on many warm-season precipitation metrics compared with ERA5, including most wet-day and hour statistics, and also adds value in the representation of wet spells in both seasons. As such, the ensemble will provide an invaluable resource for future improvements in the process understanding of the hydroclimate of this remote but important region.

Applications and advancements of nanoparticle-based drug delivery in alleviating lung cancer and chronic obstructive pulmonary disease - Gabriele De Rubis; Keshav Raj Paudel; Leander Corrie; Samir Mehndiratta; Vyoma K. Patel; Popat S. Kumbhar; Arehalli Sidramappa Manjappa; John Disouza; Vandana Patravale; Gaurav Gupta; Bikash Manandhar; Rashi Rajput; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Algae-based approaches for Holistic wastewater management: A low-cost paradigm - Simranjeet Singh; Lav Singh; Vijay Kumar; Wahid Ali; Praveen C. Ramamurthy; Daljeet Singh Dhanjal; Nikhita Sivaram; Ruby Angurana; Joginder Singh; Vimal Chandra Pandey; Nadeem A. Khan (Chemosphere, 2023)

Glomus fasciculatum an arbuscular mycorrhizal fungus alleviate the adverse effects of lead, arsenic, nickel, and improves growth parameters of Monarda citriodora Cerv.ex Lag (lemon beebalm) - Savita Luxmi; Ruby Singh; Sajad Ahmed; Sumit G. Gandhi; Rajendra Bhanwaria (Rhizosphere, 2023)

Improved and reliable plant regeneration and Agrobacterium-mediated genetic transformation in soybean (Glycine max L.) - Ruby Tiwari; Ajay K. Singh; Manchikatla V. Rajam (Journal of Crop Science and Biotechnology, 2023)

Modern biotic and abiotic analogues from the surface soil of Ganga-Ghaghara-Gandak interfluves of the Central Ganga Plain (CGP), India: Implications for the palaeoecological reconstructions - Swati Tripathi; Biswajeet Thakur; Anupam Sharma; Binita Phartiyal; Sadhan Kumar Basumatary; Ruby Ghosh; Kamlesh Kumar; M.C. Manoj; Shailesh Agrawal; Anjum Farooqui; Pooja Tiwari; Korobi Saikia; et al. (CATENA, 2023)

Cuscuta reflexa Possess Potent Inhibitory Activity Against Human Malaria Parasite: An In Vitro and In Vivo Study - Sashi Bhusan Ojha; Raj Kumar Sah; Evanka Madan; Ruby Bansal; Shaktirekha Roy; Shailja Singh; Gunanidhi Dhangadamajhi (Current Microbiology, 2023)

Last 10 millennial history of Indian summer monsoon in the Bengal region – a multi-proxy reconstruction from a lacustrine archive - Ruby Ghosh; Korobi Saikia; Oindrila Biswas; Shailesh Agrawal; P. Morthekai; Mohammad Arif; Binita Phartiyal; Anupam Sharma; Neha Singh; Dipak Kumar Paruya; Pyarimohan Maharana; Mayank Shekhar; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Classification of glacier with supervised approaches using PolSAR data - Ruby Panwar; Gulab Singh (Environmental Monitoring and Assessment, 2023)

Enhancement of output power of semitransparent photovoltaic thermal air collector using ANFIS model - Ruby Beniwal; Narendra Singh Beniwal; Hari Om Gupta (Environmental Science and Pollution Research, 2022)

Advances in Boerhaavia diffusa hairy root technology: a valuable pursuit for identifying strain sensitivity and up-scaling factors to refine metabolite yield and bioactivity potentials - Ruby Gupta; Pallavi Pandey; Sailendra Singh; Dhananjay Kumar Singh; Archana Saxena; Suaib Luqman; Dnyaneshwar U. Bawankule; Suchitra Banerjee (Protoplasma, 2016)

Squalene Synthase Gene from Medicinal Herb Bacopa monniera: Molecular Characterization, Differential Expression, Comparative Modeling, and Docking Studies - Rishi K. Vishwakarma; Krunal Patel; Prashant Sonawane; Uma Kumari; Somesh Singh; Ruby; Shakeel Abbassi; Dinesh C. Agrawal; Hsin-Sheng Tsay; Bashir M. Khan (Plant Molecular Biology Reporter, 2015)

Production of anti-cancer triterpene (betulinic acid) from callus cultures of different Ocimum species and its elicitation - Harshita Pandey; Pallavi Pandey; Sailendra Singh; Ruby Gupta; Suchitra Banerjee (Protoplasma, 2015)

Molecular cloning and characterization of genistein 4′-O-glucoside specific glycosyltransferase from Bacopa monniera - Ruby; R. J. Santosh Kumar; Rishi K. Vishwakarma; Somesh Singh; Bashir M. Khan (Molecular Biology Reports, 2014)

Eddy fluxes and sensitivity of the water cycle to spatial resolution in idealized regional aquaplanet model simulations - Samson Hagos; L. Ruby Leung; William I. Gustafson; Balwinder Singh (Climate Dynamics, 2014)

Functional Characterization of a Glucosyltransferase Specific to Flavonoid 7-O-Glucosides from Withania somnifera - R. J. Santosh Kumar; Ruby; Somesh Singh; Prashant D. Sonawane; R. K. Vishwakarma; B. M. Khan (Plant Molecular Biology Reporter, 2013)

Molecular characterization and differential expression studies of an oxidosqualene cyclase (OSC) gene of Brahmi (Bacopa monniera) - Rishi K. Vishwakarma; Prashant Sonawane; Somesh Singh; Uma Kumari; Ruby; Bashir M. Khan (Physiology and Molecular Biology of Plants, 2013)

Molecular Cloning, Biochemical Characterization, and Differential Expression of an Acetyl-CoA C-Acetyltransferase Gene (AACT) of Brahmi (Bacopa monniera) - Rishi K. Vishwakarma; Ruby; Somesh Singh; Prashant D. Sonawane; Sameer Srivastava; Uma Kumari; R. J. Santosh Kumar; Bashir M. Khan (Plant Molecular Biology Reporter, 2013)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Discrepancies in Bacterial Recovery from Dental Unit Water Samples on R2A Medium and a Commercial Sampling Device - Richard S. Smith; Silvia A. Pineiro; Ruby Singh; Elaine Romberg; Mohamed E. Labib; Henry N. Williams (Current Microbiology, 2004)

Characterization of Microbial Communities from Coastal Waters using Microarrays - O. Colin Stine; Amy Carnahan; Ruby Singh; Jan Powell; Jon P. Furuno; Alicia Dorsey; Ellen Silbergeld; Henry N. Williams; J. Glenn Morris (Environmental Monitoring and Assessment, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)